Preparing Digital Natives to Teach: Time to Redesign Teacher Education Programs - Adam C. Holden; Thomas McGlinn (The Advocate, 2012)
Since the emergence of Marc Prensky's concept of Digital Natives being taught by Digital Immigrants, education's challenge has been to find a way to effectively teach those who have grown up in a net generation. Now that the first of these millenniel students are preparing to become teachers themselves, we have the opportunity, perhaps for the first time, to witness true digital natives teaching their own. This article will examine the paradigm shift required of teacher education programs if they are to prepare this digital teaching generation effectively for the educational challenge that lies ahead of them.